SOCIO-ECONOMIC IMPLICATION OF KHAT CONSUMPTION ON THE HOUSEHOLD ECONOMY - Omar, Rashid A.; Kennedy, Mutundu K.; Mbugua, Levi N. (International Journal of Research -GRANTHAALAYAH, 2019)
This study applied exploratory-descriptive design, to determine the implication of Khat consumption on the household economy. The study was guided by both structural functionalism and conflict theories. The target population were families whose members consume Khat of which a sample of 350 respondents was obtained using snowball technique. Structured questionnaires were administered and analysed quantitatively and focus group discussions were thematically analyzed through narrative and verbatim. The study found that Khat consumption was widely accepted by all age groups and that the number of days Khat was consumed, the variety of Khat consumed, highest level of education attained by the consumer, employment status and income had negative effects on the household economy. There was a significant association between household economy and marital status (p = 0.006) as well as employment status (p < 0.0001). Khat regulation was preferred as well as community sensitization on the implication of Khat consumption.